HOW IMPORTANT IS COMMUNICATING WITH NATIVE ENGLISH SPEAKERS TO EFL LEARNERS’ SELF-CONFIDENCE IN THEIR ENGLISH LANGUAGE PROFICIENCY? - Alberth Alberth (Journey: Journal of English Language and Pedagogy, 2023)
Research evidence shows that communicating and interacting with native speakers could boost students’ self-confidence in their language proficiency. If this claim proves to be veritable, students who have the experience communicating and interacting with native speakers, either online or offline, would expectedly feel more confident than those who do not. The present study sought to examine whether significant differences existed in the selfconfidence level of EFL (English as a Foreign Language) learners who (a) had the experience communicating with native English speakers and who did not; (b) had the intention to communicate with native English speakers and who did not; (c) were males and females, and (d) who were in different academic years (year 1, year 2, and year 3 respectively). Independent samples t-test revealed that, whereas males and females were equally confident, learners who had the experience interacting, or who had the intention communicating, with native English speakers were significantly more confident in their English language proficiency than those who had never interacted, or who did not have the intention to communicate, with native English speakers. No significant differences were observed based on year of enrollment. Implications of this study on the English language teaching and learning will be critically discussed in this paper.